Perlindungan Hukum Bagi Kreditur Dalam Perjanjian Kredit Yang Terjadi Wanprestasi Di BPR Muncul Artha Sejahtera Semarang - kunarto, kunarto; Pratiwi, Febriyana Mega (Jurnal JURISTIC, 2025)
One of the efforts made by creditors to address non-performing loans is through the auction of collateral secured or encumbered by a mortgage right. This study raises two main issues: fisrt how is legal protection provided to creditors in credit agreements that experience default with collateral in the form of mortgage rights at BPR Muncul Artha Sejahtera Semarang? And second What obstacles are encountered in the implementation of legal protection for creditors in such credit agreements, and what are the solutions? This research employs a normative legal research method with a descriptive-analytical specification, aiming to describe applicable legal norms and assess their implementation without drawing general conclusions. The findings indicate that legal protection for creditors in defaulted credit agreements with mortgage collateral at BPR Muncul Artha Sejahtera Semarang is implemented through several stages: rescheduling, reconditioning of interest burden, restructuring, and the sale of the mortgage collateral. The bank encounters obstacles in executing the sale of mortgage collateral, but continues to inform the debtor, in accordance with the credit agreement, that the collateral will be sold to fulfill the debtor’s obligation to repay the debt. As a solution, the debtor is given the opportunity to settle the debt or sell the collateral independently.